Kebijakan Pengembangan Kurikulum Pendidikan Islam di Madrasah dalam Meningkatkan Kompetensi Keagamaan Siswa - Saputra, Muhammad Nur Aziz (IIQ An Nur Yogyakarta, 2025)
In this study, it aims to identify the policies that guide the construction of an Indonesian Islamic education curriculum. The methodology of research that was used in this study is descriptive review of literature, or the collection of data through scanning a variety of sources like books, peer-reviewed material, and journals. Using this descriptive analysis, researchers detail and describe information that has been collected and employ it as a tool for analysis. Based on the findings from the research, the Islamic education curriculum has transformed extensively over a span of three eras of time in the past. There were three political phases which could be discerned during Indonesia's curriculum development. Firstly, there were three revisions of the curriculum in 1947, 1952, and 1964 that launched the beginning of the Old Order era. Second, there were four revisions during the New Order: in 1968, 1975, 1984, and 1994. Third, there were four reforms during the Reformation era: the K–13 Curriculum of 2013; the School Level Curriculum (KTSP) of 2006; the Competency-Based Curriculum (KBK) of 2004; and the Merdeka Curriculum that was in place until now.